Long-term heart-specific mortality among 347 476 breast cancer patients treated with radiotherapy or chemotherapy: a registry-based cohort study - Weberpals, Janick; Müller, Oliver J.; Brenner, Hermann (European heart journal, 2018)
Aims: Breast cancer survival has improved throughout the last decades, but treatment-induced cardiotoxicity remains a major concern. This study aimed to investigate competing causes of death and prognostic factors within a large cohort of breast cancer patients and to describe the heart-specific mortality in relation to the general population. Methods and results: In this registry-based cohort study, women diagnosed with breast cancer between 2000 and 2011, who were treated with radiotherapy or chemotherapy and followed until 2014, were identified from the Surveillance, Epidemiology, and End Results-18 (SEER-18) database. Cumulative mortality functions were computed. To investigate heart-specific mortality relative to the general population, long-term (≥10 years) standardized mortality ratios (SMRs) were calculated. Prognostic factors for heart-specific mortality were assessed by calculating cause-specific hazard ratios (HRcs) with corresponding 95% confidence intervals using the Cox proportional hazards regression. Subgroup analysis on intermediate-term mortality according to molecular subtypes, for which information was available since 2010, was performed. In total, 347 476 breast cancer patients were eligible to be included in the study. Among all possible competing causes of death, breast cancer accounted for the highest cumulative mortality. Compared with the general population, heart-specific mortality of breast cancer patients treated with radiotherapy or chemotherapy was lower [SMRoverall 0.84 (0.79-0.90)]. In subgroup analysis, human epidermal growth factor receptor 2 (HER2)-positive subtype was not associated with increased heart-specific mortality relative to HER2-negative patients [HRcs 0.96 (0.70-1.32)]. Conclusion: Heart-specific mortality among breast cancer survivors is not increased compared with the general population. Human epidermal growth factor receptor 2-positive patients do not have increased heart-specific mortality compared to HER2-negative patients.
Gesehen am 08.02.2019